2008
DOI: 10.1111/j.1365-2702.2007.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music therapy on psychological health of women during pregnancy

Abstract: The findings can be used to encourage pregnant women to use this cost-effective method of music in their daily life to reduce their stress, anxiety and depression. Further research is needed to test the long-term benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
1
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 36 publications
3
158
1
13
Order By: Relevance
“…Women who are prone to become too anxious are the ones that should benefit the most. Other authors have reported similar results with music listening, concerning the psychological well-being, but not cortisol on pregnant women (Browning, 2000;Sidorenko, 2000;Chang and Chen, 2005;Chang et al, 2008).…”
Section: Interventionsupporting
confidence: 55%
See 1 more Smart Citation
“…Women who are prone to become too anxious are the ones that should benefit the most. Other authors have reported similar results with music listening, concerning the psychological well-being, but not cortisol on pregnant women (Browning, 2000;Sidorenko, 2000;Chang and Chen, 2005;Chang et al, 2008).…”
Section: Interventionsupporting
confidence: 55%
“…Non-pharmacological therapies should be considered as possible choices for pregnant women attempting to avoid medication side-effects. These include psychotherapy, massage therapy, yoga, and listening to music (Cunningham and Zayas, 2002;Narendran et al, 2005;Chang et al, 2008;Kimber et al, 2008;Maharana et al, 2009;Field et al, 2009Field et al, , 2010, the latter being probably the most accessible non-pharmacological therapy for low socioeconomic status women. Yoga, also a potentially accessible therapy, reduces sympathetic activity improving autonomic responses to stress in normal pregnant women (Maharana et al, 2009) but its practice is not well accepted in all cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings resonate through the literature where a variety of authors have found that exposure to a music intervention during pregnancy benefits women in terms of stress reduction. This effect is seen antenatally (Chang et al, 2008), during hospitalisation (Sidorenko, 2000), during caesarean section (Chang and Cheng, 2005) and during labour (Tabarro et al, 2010). Chang et al, (2008), for example, trialled a music intervention where pregnant women listened to pre-recorded lullabies and classical music over a 2 week period.…”
Section: Relaxation and Stress Reductionmentioning
confidence: 99%
“…This effect is seen antenatally (Chang et al, 2008), during hospitalisation (Sidorenko, 2000), during caesarean section (Chang and Cheng, 2005) and during labour (Tabarro et al, 2010). Chang et al, (2008), for example, trialled a music intervention where pregnant women listened to pre-recorded lullabies and classical music over a 2 week period. They found that this intervention resulted in significant psychological benefits for the women.…”
Section: Relaxation and Stress Reductionmentioning
confidence: 99%
See 1 more Smart Citation